Environmental Radioactivity and Emergency Preparedness - Isaksson, Mats, 1961-, author 642616; Rääf, Christopher L., 1968-, author 642618 (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
"This book presents the radiological sources that could be a threat to humans and the environment. It discusses how to deal with this threat in terms of measurements, prospective models, and regulations. The transport of radioactive substances in ecosystems is discussed, together with remedial actions in case an accident should happen. The book covers radiation sources, measurement methods, modeling, and calculations, as well as strategies in emergency preparedness (including strategies for first-responders and radiological triage)"--